Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Sure! Let's find the solutions to the equation [tex]\( 12x^3 - 24x^2 + 12x = 0 \)[/tex].
1. Factor out the greatest common factor (GCF):
The GCF of the terms [tex]\(12x^3\)[/tex], [tex]\( -24x^2\)[/tex], and [tex]\( 12x \)[/tex] is [tex]\(12x\)[/tex]. So we factor [tex]\(12x\)[/tex] out of the equation:
[tex]\[ 12x(x^2 - 2x + 1) = 0 \][/tex]
2. Simplify the equation:
Now, we have:
[tex]\[ 12x(x^2 - 2x + 1) = 0 \][/tex]
3. Break the equation into separate factors:
For the product to be zero, at least one of the factors must be zero. So we have two potential cases:
[tex]\[ 12x = 0 \quad \text{or} \quad x^2 - 2x + 1 = 0 \][/tex]
4. Solve the first factor:
For [tex]\(12x = 0\)[/tex]:
[tex]\[ x = 0 \][/tex]
5. Solve the second factor:
We need to solve [tex]\(x^2 - 2x + 1 = 0\)[/tex]. This is a quadratic equation that can be factored as follows:
[tex]\[ (x - 1)^2 = 0 \][/tex]
Setting the factor equal to zero gives us:
[tex]\[ x - 1 = 0 \implies x = 1 \][/tex]
6. Combine the solutions:
The solutions to the equation [tex]\( 12x^3 - 24x^2 + 12x = 0 \)[/tex] are thus:
[tex]\[ x = 0 \quad \text{or} \quad x = 1 \][/tex]
Therefore, the solutions to the equation [tex]\( 12x^3 - 24x^2 + 12x = 0 \)[/tex] are [tex]\( \boxed{0 \text{ and } 1} \)[/tex].
1. Factor out the greatest common factor (GCF):
The GCF of the terms [tex]\(12x^3\)[/tex], [tex]\( -24x^2\)[/tex], and [tex]\( 12x \)[/tex] is [tex]\(12x\)[/tex]. So we factor [tex]\(12x\)[/tex] out of the equation:
[tex]\[ 12x(x^2 - 2x + 1) = 0 \][/tex]
2. Simplify the equation:
Now, we have:
[tex]\[ 12x(x^2 - 2x + 1) = 0 \][/tex]
3. Break the equation into separate factors:
For the product to be zero, at least one of the factors must be zero. So we have two potential cases:
[tex]\[ 12x = 0 \quad \text{or} \quad x^2 - 2x + 1 = 0 \][/tex]
4. Solve the first factor:
For [tex]\(12x = 0\)[/tex]:
[tex]\[ x = 0 \][/tex]
5. Solve the second factor:
We need to solve [tex]\(x^2 - 2x + 1 = 0\)[/tex]. This is a quadratic equation that can be factored as follows:
[tex]\[ (x - 1)^2 = 0 \][/tex]
Setting the factor equal to zero gives us:
[tex]\[ x - 1 = 0 \implies x = 1 \][/tex]
6. Combine the solutions:
The solutions to the equation [tex]\( 12x^3 - 24x^2 + 12x = 0 \)[/tex] are thus:
[tex]\[ x = 0 \quad \text{or} \quad x = 1 \][/tex]
Therefore, the solutions to the equation [tex]\( 12x^3 - 24x^2 + 12x = 0 \)[/tex] are [tex]\( \boxed{0 \text{ and } 1} \)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.